MOBILE OFFENSES AND SPACING - Itoudis, Dimitris (Sport- és Egészségtudományi füzetek, 2026)
The calls we use in a season are between 100 and 105, including inbound and after time out plays. We use direct and mobile plays but always decide which plays will be in the game plan. All the offence coaches choose need to have some logic. In our playbook, we use a play called Two Down, which we can use in any category. This play has several countermoves and adjustments depending on the opponent’s defence against us. It requires five players to be mobile and active at all times to use it as an advantage. Each player moves at the same time, creating multiple options to score. This play’s adjustments mainly depend on the quality of our players and their dominant hand.